Potential miRNA-disease association prediction based on kernelized Bayesian matrix factorization - Chen, Xing; Li, Shao-Xin; Yin, Jun; Wang, Chun-Chun (Genomics (San Diego, Calif.), 2020)
Many biological experimental studies have confirmed that microRNAs (miRNAs) play a significant role in human complex diseases. Exploring miRNA-disease associations could be conducive to understanding disease pathogenesis at the molecular level and developing disease diagnostic biomarkers. However, since conducting traditional experiments is a costly and time-consuming way, plenty of computational models have been proposed to predict miRNA-disease associations. In this study, we presented a neoteric Bayesian model (KBMFMDA) that combines kernel-based nonlinear dimensionality reduction, matrix factorization and binary classification. The main idea of KBMFMDA is to project miRNAs and diseases into a unified subspace and estimate the association network in that subspace. KBMFMDA obtained the AUCs of 0.9132, 0.8708, 0.9008±0.0044 in global and local leave-one-out and five-fold cross validation. Moreover, KBMFMDA was applied to three important human cancers in three different kinds of case studies and most of the top 50 potential disease-related miRNAs were confirmed by many experimental reports. •The computational model made use of Bayesian inference and dimensionality reduction.•The AUCs of LOOCV and 5-fold cross validation were significantly better than many previous computational models.•Three case studies for important human diseases were performed.•KBMFMDA could be a reliable method for miRNA-disease association prediction.